Complete biology for Cambridge Secondary 1 : Cambridge checkpoint and beyond - Large, Pam (Oxford : Oxford University Press, 2014)
This brand new course builds in crucial challenge material right from the start, enabling students to confidently leap into Cambridge IGCSERG Science study with a solid foundation in Biology. It is the best preparation for our bestselling Complete Science for Cambridge IGCSE course,facilitating seamless progression from Cambridge Secondary 1 Stage 9 right into Complete Biology for Cambridge IGCSE. Complete Biology for Cambridge Secondary 1 covers all three years of Cambridge Secondary 1 Biology in the same book, flowing smoothly from one stage to the next. Regular revision andextension exercises will help consolidate learning and then stretch and challenge students to reach the next level. Plus, it's endorsed by Cambridge International Examinations, so you know it's comprehensive.